MATHEMATICAL MODEL FOR CALCULATING THE PARAMETERS OF ELECTROMECHANICAL SHOCK-ABSORBER OF THE TRAM RUNNING GEAR (Transport systems and technologies, 2018)
The development of urban electric transport is of great importance to any country in the world. Modern designs of city electric transport emphasize the city's infrastructure, increase ecology and traffic safety, smooth running and economic efficiency of passenger transportation. The tram having a low floor level corresponds to the specified criteria for the operation of electric transport.In the work the analysis of researches on the elements of tram running gear and certain problems which are solved by some technical solutions is carried out.The purpose of the work is to determine the possibility of using an electromechanical shock-absorber in the design of tram’s bogie running gear.The scientific novelty of the work is in the possibility of using an electromechanical shock-absorber for all types of converters and this does not come within the existing classification of other designs. For the first time, a simplified mathematical model for calculating the parameters of an electromechanical shock-absorber has been developed and its characteristics have been determined. To prove the provisions and adequacy of the mathematical model, a set of digital experiments was conducted in the FEMM environment. For the first time, the distribution of the magnetic field pattern has been obtained, depending on the working stroke of the shock-absorber rod at the required intervals.The practical value of a technical solution is the ability to control the damping force depending on the modes of motion of the vehicle, and to recover the energy of the electromechanical shock-absorber for its re-use in the vehicle.
Keywords: electromechanical shock-absorber, electromechanical converter, spring increase, running gear, pneumatic springs